VALIDITAS MODUL MATEMATIKA KELAS X SMA DENGAN MENERAPKAN VARIASI MODEL PEMBELAJARAN KOOPERATIF - Tetty Natalia Sipayung; Sinta Dameria Simanjuntak (Universitas Islam Sumatera Utara, 2017)
This research which is entitled as a grade X of Senior High School by applying variations of cooperative learning model on each presented material. The research method used is a research development method which is used to produce a developed module and to test the effectiveness. The validity of module in this research is based on the feasibility of the standard of the media and material. The media feasibility standard of the module consists of aspects of both in graphs and language. The module eligibility standart includes the feasibility aspects of the contents, presentation and contextual assessment. The average score for the aspect of feasibility in graph value is 3.95, the language value is 3.93, the content value aspect is 3.99, and the aspect of valuation of contextual is 4. Thus, the mathematics module for grade X of Senior High School which is developed in this research is valid.